2023
DOI: 10.1038/s41598-023-35665-9
|View full text |Cite
|
Sign up to set email alerts
|

Fish biodiversity declines with dam development in the Lower Mekong Basin

Abstract: Hydropower dams are a source of renewable energy, but dam development and hydropower generation negatively affect freshwater ecosystems, biodiversity, and food security. We assess the effects of hydropower dam development on spatial–temporal changes in fish biodiversity from 2007 to 2014 in the Sekong, Sesan, and Srepok Basins—major tributaries to the Mekong River. By analyzing a 7-year fish monitoring dataset, and regressing fish abundance and biodiversity trends against cumulative number of upstream dams, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Aside from drought, streamflow alteration is caused by anthropogenic activities such as hydropower dam operations and water extraction for agricultural irrigation [57]. For instance, summer baseflow in dammed rivers is generally higher than free-flowing rivers [18,58], which is the case for the Sesan River [12]. Li et al [18] and Wild et al [58] reported that dams have significantly decreased streamflow in the wet season in the Mekong River and Tonle Sap Lake, and increased streamflow in the dry season.…”
Section: Drought In Regulated Watershedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from drought, streamflow alteration is caused by anthropogenic activities such as hydropower dam operations and water extraction for agricultural irrigation [57]. For instance, summer baseflow in dammed rivers is generally higher than free-flowing rivers [18,58], which is the case for the Sesan River [12]. Li et al [18] and Wild et al [58] reported that dams have significantly decreased streamflow in the wet season in the Mekong River and Tonle Sap Lake, and increased streamflow in the dry season.…”
Section: Drought In Regulated Watershedsmentioning
confidence: 99%
“…A major tributary system of the LMB is formed by the Sekong, Sesan, and Srepok Rivers (the 3S Basin), which contribute up to 25% of streamflow and sediment to the mainstem Mekong River [11]. This basin is currently experiencing hydrologic alteration due to rapid hydropower development [12]. The 3S Basin has 51 operational dams as of 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of 2021, at least 51 dams were operating in the 3S Basin, with a combined generating capacity of 4,684 MW. The Sesan River has the most dams of the three basins, with 22 dams, and the Sekong has the fewest dams, with 14 dams [32]. Given on-going hydropower dam development, streamflow in 3S rivers have deviated from natural regimes [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…de Silva et al found that in Asia, since 1700, more than 64% of suitable elephant habitat has been lost in conjunction with land use practices for agricultural purposes 10 . Finally Sor et al show how in the Lower Mekong Basin, dams built to produce renewable hydropower reduce fish biodiversity 11 . They therefore recommend using existing dams rather than building new ones, as well as diversification in the development and use of renewable energy sources.…”
mentioning
confidence: 99%